Cover Image. (24th January 2020) - Dai, Zhiwen; Wang, Chenglong; Zhang, Dalin; Tian, Wenxi; Qiu, Suizheng; Su, Guanghui
Abstract : The cover image is based on the Research Article Thermoelectric characteristics analysis of thermionic space nuclear power reactor by Zhiwen Dai et al., https://doi.org/10.1002/er.4926 .